A quantitative study: Can information system strategy boost performance in private higher education? - Munawar, Asep; Suryana; Disman; Hendrayati, Heny (Indonesian Research Journal in Education |IRJE|, 2025)
This research aims to examine the influence of Information Systems Strategy (ISS) and Digital Transformation (DT) on the performance of private universities amidst theoretical findings suggesting that ISS and DT are influenced by internal factors Management Capability (MC) and external factors Government Business Support (GBS). A quantitative approach survey technique was used with the involvement of 92 private universities in the LLDIKTI Region IV West Java and Banten participating as research samples. The test method adopts the partial least square (PLS) structural equation modeling (SEM) model. The results showed that there is a positive significance of management capability on university performance-both directly and through information systems strategy and digital transformation. This finding emphasizes that capable management can project the formulation and formulate and organize the implementation of an effective information technology strategy, as well as drive a strategy, as well as drive an appropriate digital transformation process.